A decentralized scalable security framework for end‐to‐end authentication of future IoT communication. Issue 12 (29th November 2019) - Sheron, P.S. Febin; Sridhar, K.P.; Baskar, S.; Shakeel, P. Mohamed
Abstract: The development of Internet of Things (IoT) has granted multiple interoperable features for user to digital things communication. The future communication technology and service provisioning in IoT is large scaling an open environment. The large scale IoT environment is supported by sensor network and independent nodes. The intelligent computing, storage, and computation features of the nodes are inherited by the IoT paradigm for its application and service support. In such an open environment, security is a prominent issue that must be administered in a decentralized manner. In this manuscript, a decentralized and scalable security framework for future IoT is designed. This framework exploits the advantages of intelligent computing and tree‐based hash for device and request authentication to provide device‐to‐device security. The tree‐based hash is used for authenticating requests and the central authority–based security feature of the framework provides device level security, ensuring better privacy and integrity in communications. The experimental analysis of the proposed security framework is analyzed in terms of detection rate, communication loss, disconnection ratio, and delay. Abstract : The decentralized and scalable security framework(DSSF) is implemented between IoT devices, access layer components, and the cloud resources. It controls the communication requirements and administers security for users and application. The concept of blockchain is inherited by the sensor nodes and devices directly from the security administered in the IoT environment. The security grating process is separated between device level and request/resource message level.